2024
DOI: 10.1037/ebs0000315
|View full text |Cite
|
Sign up to set email alerts
|

Examining the interaction between altruism and resource potential in heterosexual women's mate preferences.

Abstract: Previous research has shown that altruism is an important trait in romantic relationships, particularly in longer relationships, where it can signal the underlying characteristics (e.g., kindness) that are valued in good partners/parents. Further evidence of this has been observed when comparing the interaction between altruism and other traits (e.g., physical attractiveness) that may signal other qualities (e.g., good genes), where altruism was preferred by heterosexual women in long-term partners. To further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Research has found that both men and women prefer altruistic partners (Bhogal et al, 2020; Moore et al, 2013), and this is particularly important when seeking a long-term relationship (Farrelly, 2013; Farrelly et al, 2016; Skilton & Farrelly, 2022). Preference for an altruistic partner has also been found to be somewhat stronger in women than in men (Farrelly et al, 2007; Phillips et al, 2008).…”
mentioning
confidence: 99%
“…Research has found that both men and women prefer altruistic partners (Bhogal et al, 2020; Moore et al, 2013), and this is particularly important when seeking a long-term relationship (Farrelly, 2013; Farrelly et al, 2016; Skilton & Farrelly, 2022). Preference for an altruistic partner has also been found to be somewhat stronger in women than in men (Farrelly et al, 2007; Phillips et al, 2008).…”
mentioning
confidence: 99%